Expression of collagen XVII and ubiquitin-binding protein p62 in motor neuron disease - Seppänen, Allan; Pikkarainen, Maria; Hartikainen, Päivi; Hofmann, Silke C.; Majamaa, Kari; Alafuzoff, Irina (Brain research, 2009)
Collagen involvement in motor neuron disease has been suggested by several earlier studies. Recently, we found collagen XVII to be expressed in locations in the human brain that include those damaged in motor neuron disease. In this study, we examined the extent of motor neuron disease-related changes in the brain of 9 subjects using ubiquitin-binding protein p62/sequestosome 1 (p62) immunohistochemistry. We then assessed whether or not the expression of collagen XVII was altered in relation to the p62 immunoreactive lesions. We found that neuronal collagen XVII expression in motor neuron disease remains similar to that seen in the normal human brain and thus a change in collagen XVII expression is not an immunohistochemically detectable feature of motor neuron disease. We also found that the regional distribution of p62 varied according to clinical presentation: p62 immunoreactive inclusions were found in the frontal cortex, hippocampus and cerebellum only in subjects with a history of psychiatric morbidity. Our study supports the re-definition of motor neuron disease as a multisystem disorder with a wide clinicopathological spectrum, and we advocate addressing psychiatric symptomology in future studies of motor neuron disease.